Diseño de un sistema de costo estandar para la prestación del servicio de la Empresa de Transporte Zavala Cargo S.A.C. - Javier Lezama, Carlos Eduardo (2015)
This research, entitled "" DESIGN SYSTEM COST STANDARD FOR THE PROVISION OF SERVICE transport company ZAVALA CARGO SAC "" has been prepared for two purposes: the first is to contribute to the company Transport " Zavala cargo SAC "has the proper use of a standard cost system which allows to standardize in an efficient, effective and timely costs incurred in the loading, transport and delivery of goods, the second is to consider students accounting degree and the general public study and application of standard cost system in similar activities. This research helps people responsible for making decisions in calculating total costs in the process of service activity land freight transport, from the point of collection to the point of delivery of goods; encourage the search for new strategies for cost reduction in transportation service. These contributions will enable Transport Management "Zavala Cargo S.A.C," perform efficiently and effectively managing resources economically.